2022
DOI: 10.1002/jnr.25062
|View full text |Cite
|
Sign up to set email alerts
|

The effects of noninvasive brain stimulation on heart rate and heart rate variability: A systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 231 publications
(336 reference statements)
1
30
0
3
Order By: Relevance
“…Neuromodulation of the left dorsolateral prefrontal cortex seems to present the potentiality to decrease the recovery time of the neurological disabilities generated by SARS-CoV-2 through different mechanisms 2 . The sympathetic and parasympathetic autonomic nervous system response seems to be involved in inflammatory modulation 4 . It is important to mention that in experimental models and preliminary data in human beings, vagus nerve stimulation attenuates inflammation, modulating activity of cholinergic anti-inflammatory pathways 5 .…”
Section: Transcranial Direct Current Stimulation Associated With Phar...mentioning
confidence: 99%
“…Neuromodulation of the left dorsolateral prefrontal cortex seems to present the potentiality to decrease the recovery time of the neurological disabilities generated by SARS-CoV-2 through different mechanisms 2 . The sympathetic and parasympathetic autonomic nervous system response seems to be involved in inflammatory modulation 4 . It is important to mention that in experimental models and preliminary data in human beings, vagus nerve stimulation attenuates inflammation, modulating activity of cholinergic anti-inflammatory pathways 5 .…”
Section: Transcranial Direct Current Stimulation Associated With Phar...mentioning
confidence: 99%
“…The heart rate (HR) regulation involves a number of hierarchical levels from the inner nervous system of the heart to cerebral cortex (Palma and Benarroch, 2014;Schmaußer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that brain-heart communication might regulate the level of cortisol in hypothalamic-pituitary-adrenal (HPA) axis activity via an indirect pathway to affect the cardiovascular system (7,8). As outcome measures for evaluating the cardiac response, heart rate (HR) and heart-rate variability (HRV) have emerged as key parameters that reflect autonomic nervous system activity and cardiovascular health status (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the involvement of some of these cortical regions in cardiovascular regulation, non-invasive brain stimulation (NIBS) may be useful to study their effects as a practical tool to investigate cardiac responses (9). Transcranial direct current stimulation (tDCS), a NIBS technique, could induce a long-term potentiation (LTP)-like facilitation or long-term depression (LTD)-like suppression (17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation